1998
DOI: 10.1017/s1092852900007239
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Function and Economic Costs of Obsessive-Compulsive Disorder

Abstract: The study presented was conducted to analyze the effects of obsessive-compulsive symptoms on patients' quality of life and the costs incurred by patients and society for the treatment of obsessive-compulsive disorder (OCD). To accomplish this, a detailed 410-item questionnaire of psychosocial function and economic cost was sent to every fourth member of the Obsessive Compulsive Foundation. Of the 2,670 members who received the survey, 701 (26.9%) returned it.Outcome measures included symptomatology, course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
7

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 16 publications
3
60
0
7
Order By: Relevance
“…Although studies of small OCD samples have reported PG rates ranging from 2.2% to 2.6% [14,15], a recently completed study of a large sample of subjects who had primary OCD (n = 293) found rates of current (0.3%) and lifetime (1.0%) PG [16] that were no greater than those in the general population (0.7-1.6%) [13]. These recent findings are consistent with those from a sample of more than 2000 individuals who had OCD in which both current and past rates of PG were lower than 1% [17]. Similarly, a family study of OCD probands did not find evidence of a significant relationship between OCD and PG or OCD and ICDs in general (with the exception of grooming and eating disorders) [18].…”
Section: Pathological Gamblingsupporting
confidence: 66%
“…Although studies of small OCD samples have reported PG rates ranging from 2.2% to 2.6% [14,15], a recently completed study of a large sample of subjects who had primary OCD (n = 293) found rates of current (0.3%) and lifetime (1.0%) PG [16] that were no greater than those in the general population (0.7-1.6%) [13]. These recent findings are consistent with those from a sample of more than 2000 individuals who had OCD in which both current and past rates of PG were lower than 1% [17]. Similarly, a family study of OCD probands did not find evidence of a significant relationship between OCD and PG or OCD and ICDs in general (with the exception of grooming and eating disorders) [18].…”
Section: Pathological Gamblingsupporting
confidence: 66%
“…People with the disorder have long delays in accessing effective treatments-17 years on average in one study. 4 They frequently present to non-psychiatrists for treatment (table 1), and psychiatric symptoms go undetected. Greater awareness of the condition is needed in a range of non-psychiatric healthcare settings, and clinicians need to be confident about recognising it.…”
Section: Why Do Clinicians Need To Know About It?mentioning
confidence: 99%
“…Desconhecimento e medo podem ainda contribuir para a demora em buscar ajuda. Hollander et al (1996Hollander et al ( , 1997 estimaram em 10 anos o tempo médio até o tratamento e em 17 anos a demora até a obtenção de tratamento adequado, o que, sem dúvida, prolonga o sofrimento. Além disso, sabe-se que alguns casos não melhoram substancialmente com o tratamento, mesmo que adequado, e que os efeitos colaterais dos psicofármacos também podem afetar a QV .…”
Section: Peculiaridades Do Transtorno Obsessivo-compulsivounclassified
“…Dessa forma, seriam conseqüências comuns do TOC, apontadas por diferentes autores (Steketee et al, 1987;Hollander et al, 1996Hollander et al, , 1997Stein et al, 2000;Lochner et al, 2003;Moritz et al, 2005;Eisen et al, 2006): diminuição da auto-estima e do bem-estar subjetivo, interferência negativa na vida estudantil, profissional, familiar, afetiva e social, com menos conquistas acadê-micas, menores aspirações de carreira, dificuldades de relacionamento, menos amigos, menor capacidade para apreciar atividades de lazer, além dos custos indiretos para a família e para a sociedade. Em casos graves, pode haver dificuldade ou incapacidade completa para atividades diárias rotineiras e alguns portadores podem ficar totalmente presos em casa, em função de comportamentos de esquiva dos estímulos temidos.…”
Section: Peculiaridades Do Transtorno Obsessivo-compulsivounclassified
See 1 more Smart Citation